Barriers to internationalization: Firm-level evidence from Germany - Christian Arndt; Claudia M. Buch; Anselm Mattes (Institut für Angewandte Wirtschaftsforschung (IAW), 2009)
Exporters and multinationals are larger and more productive than their domestic counterparts. In addition to productivity, financial constraints and labor market constraints might constitute barriers to entry into foreign markets. We present new empirical evidence on the extensive and intensive margin of exports and FDI based on detailed micro-level data of German firms. Our paper has three main findings. First, in line with earlier literature, we find a positive impact of firm size and productivity on firms' international activities. Second, small firms suffer more frequently from financial constraints than bigger firms, but financial conditions have no strong effect on internationalization. Third, labor market constraints constitute a more severe barrier to foreign activities than financial constraints. Being covered by collective bargaining particularly impedes international activities.
Keywords: F2; G2; 330; foreign direct investment; exports; firm heterogeneity; productivity; financial constraints; labor market constraints; Multinationales Unternehmen; Internationale Markteintrittsstrategie; Direktinvestition; Exportindustrie; Produktivität; Betriebsgröße; Verschuldungsrestriktion; Arbeitsmarktflexibilisierung; Schätzung; Deutschland